2020
DOI: 10.1038/s41375-020-01049-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of deep responders to carfilzomib-based therapy: a subgroup analysis from ASPIRE and ENDEAVOR

Abstract: To understand the profile of best responders (complete response or better [≥CR]) to carfilzomib, we described the characteristics, progression-free survival (PFS), overall survival (OS) data, and the safety of patients who achieved ≥CR to carfilzomib-based treatment in ASPIRE and ENDEAVOR. In post hoc analyses from ASPIRE and ENDEAVOR, median PFS and OS were longer for ≥CR patients versus those who achieved a very good partial response or partial response (VGPR/PR). In the carfilzomib arm of ASPIRE, median PFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The incidence of both hematologic and nonhematologic grade ≥3 AEs and SAEs were similar across all dose levels, suggesting that escalating doses of carfilzomib had little impact on the underlying toxicity of the VXLD regimen. The safety profile across the dose levels was similar to that of other contemporary relapsed regimens 15,25–28 …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The incidence of both hematologic and nonhematologic grade ≥3 AEs and SAEs were similar across all dose levels, suggesting that escalating doses of carfilzomib had little impact on the underlying toxicity of the VXLD regimen. The safety profile across the dose levels was similar to that of other contemporary relapsed regimens 15,25–28 …”
Section: Discussionmentioning
confidence: 52%
“…The safety profile across the dose levels was similar to that of other contemporary relapsed regimens. 15,[25][26][27][28] PK results demonstrated that carfilzomib exposure adjusted for body surface area was similar between adults and children and across different age groups of children, at least for patients 1 year of age and above. A limited set of proteasome inhibition data indicated that proteasome activity in peripheral blood was completely suppressed 2 hours after the first target dose of carfilzomib at doses of 36 mg/m 2 and higher, and remained at least partially suppressed compared to baseline, on day 29 of induction.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations were performed with this model to compare the average proteasome inhibition across five cycles of treatment for the 70 QW and 56 BIW regimens. Five cycles (i.e., five months) of treatment was chosen to represent a time frame in which subjects could achieve the deepest degrees of response, based on the median time to response data in the phase III ARROW and ENDEAVOR studies [ 11 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A subgroup analysis of the ASPIRE and ENDEAVOR trials showed that addition of CFZ improved ORR and PFS, regardless of whether patients had an early or late relapse following their most recent prior therapy [ 28 ]. A different subgroup analysis of the two trials found no association between cytogenetic risk and reaching complete response or better (≥CR) [ 29 ]. At present, CFZ is approved as a single agent for patients who have received ≥ 1 prior therapies or as combination with 1.…”
Section: Available Therapeutic Modalitiesmentioning
confidence: 99%